2004
DOI: 10.1074/jbc.m402567200
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin Activation Exposes a Key Hydrophobic Binding Site for the Transducin α-Subunit C Terminus

Abstract: Conformational changes enable the photoreceptor rhodopsin to couple with and activate the G-protein transducin. Here we demonstrate a key interaction between these proteins occurs between the C terminus of the transducin ␣-subunit (G T␣ ) and a hydrophobic cleft in the rhodopsin cytoplasmic face exposed during receptor activation. We mapped this interaction by labeling rhodopsin mutants with the fluorescent probe bimane and then assessed how binding of a peptide analogue of the G T␣ C terminus (containing a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
145
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 59 publications
13
145
0
Order By: Relevance
“…2C Right). This type of interaction is consistent with experimental results that have already revealed a hydrophobic contribution to R*-G␣CT interaction (23). In the I-interaction, only 31% (892 Å 2 ) of the solvent accessible surface of ␣5 is excluded from the solvent.…”
Section: Kinetic Analysis: Intermediary Interaction Between Gt⅐gdp Ansupporting
confidence: 79%
“…2C Right). This type of interaction is consistent with experimental results that have already revealed a hydrophobic contribution to R*-G␣CT interaction (23). In the I-interaction, only 31% (892 Å 2 ) of the solvent accessible surface of ␣5 is excluded from the solvent.…”
Section: Kinetic Analysis: Intermediary Interaction Between Gt⅐gdp Ansupporting
confidence: 79%
“…The crystal structure of bovine rhodopsin shows that the cytoplasmic ends of helix V and VI are prominently extended below the plasma membrane in two different crystal forms, and these extended regions are highly flexible according to crystallographic temperature factors at more than 100 Å 2 (22,37). In rhodopsin, it has also been suggested that this region of helix V and the membrane-proximal region of helix VI function in activation of transducin via a carboxyl-terminal region of G␣ t (27,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…By the significant rearrangement of loop C3 due to helix movement of TM5 and TM6, some residues in C3 are exposed, i.e. Leu-226, Phe-228 and Thr-229 on TM5, Ser-240 in C3, and Thr-242, Thr-243 and Met-253 on TM6 [127].…”
Section: Figure 38 "Ionic Lock" Of Opsin and Photoactivated Rhodopsmentioning
confidence: 99%